Desulfurization Capabilities of Indigenous Bacteria Isolates for Enhanced Sulfur Removal - Emmanuela Kwao-Boateng; Kwabena Danquah; Emmanuel Ankudey; Lawrence Darkwah; Derrick Boateng (Journal of Chemical and Petroleum Engineering)
Desulfurization is an essential part of refinery operations due to the numerous effects of sulfur on refinery equipment and fuel product quality. Biocatalytic desulfurization methods potentially promote energy savings due to the mild temperature, and low-pressure operating conditions involved. Furthermore, the biological process results in a negligible level of undesirable products and emissions without lowering the calorific value of the fuel. In this study, indigenous microorganisms that thrive in hydrocarbon environments were isolated, characterized, and identified from waste oil dump sites at major garages in the Kumasi Metropolis, Ghana, and used to desulfurize crude oil.  Preliminary screening resulted in 132 microbial isolates with 26 most potent isolates selected for the final identification and their use for desulfurization.  The isolates identified included Stenotrophomonas maltophilia, pseudomonas aeruginosa, alcaligenes faecalis, enterococcus faecalis, xanthomonas maltophilia, pseudomonas maltophilia, and pseudomonas putida. The highest level of desulfurization was 73.5% at 40 ℃ by stenotrophomonas maltophilia. An isolate of Enterococcus faecalis, which has not been widely explored for its sulfur removal potential could remove 61% sulfur from crude oil and is worth further research.